Food Additives: Importance, Classification, and Adverse Reactions in Humans - Florez-Mendez, J (Springer International Publishing, 2022)
Food additives (FAs) are defined as substances not normally found in foods. These compounds have been used to improve the nutritional value, flavor, and texture of foods, or to preserve them. There is a wide list based on natural (NFAs) and synthetic (SFAs) food additives used as preservatives. Nowadays, the search for natural alternatives has been stimulated by a change in the food consumption habits of consumers. Concretely, more people prefer foods free from SFAs, which has led to an increase in the consumer demand for healthier food products with a clean label over the last few years. Based on the literature, SFAs can be associated with the development of human diseases, and therefore NFAs have promising food applications. However, most NFAs are highly unstable when applied to foods, and could alter food taste and smell. This chapter deals with the importance of using FAs and provides a comprehensive review of the additive classification, focusing on the use of NFAs versus SFAs and their adverse reactions in humans. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.